Universal salvation in late antiquity Porphyry of Tyre and the Pagan-Christian debate - Simmons, Michael Bland (Oxford Univ. Press, 2015)
This title explores the background to the effort of the Neoplatonist philosopher Porphyry (c.A.D. 232-305) to devise a system of universal salvation as a means of countering the Christian soteriological challenge, and the Christian reactions to this, notably from Eusebius of Caesarea.
Literaturverz. s. 397 - 477
Keywords: Porphyrius -- 233-301; Soteriologie